2015
DOI: 10.1063/1.4926420
|View full text |Cite
|
Sign up to set email alerts
|

Review and test of methods for determination of the Schottky diode parameters

Abstract: This paper deals with the extraction of the Schottky diode parameters from a current-voltage characteristic. 10 analytical methods, 2 numerical methods, and 4 evolutionary algorithms of the series resistance, barrier height, and ideality factor determination are reviewed. The accuracy of the methods is quantified using a wide range of both ideal and noisy synthetic data. In addition, the influencing factors of the parameters extraction accuracy are estimated. The adaptive procedure, which improves the precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We used I-V data below and around , and followed the Cheung method [30][31] to extract and at a given temperature from the slope and the intercept of the corresponding (ln ) ⁄ vs.…”
Section: Fig 3cmentioning
confidence: 99%
“…We used I-V data below and around , and followed the Cheung method [30][31] to extract and at a given temperature from the slope and the intercept of the corresponding (ln ) ⁄ vs.…”
Section: Fig 3cmentioning
confidence: 99%
“…It is worth noting that in the literature is reported that to extract the four parameters, by means of only the direct I-V characteristic, is difficult and cumbersome. This is an active area of research, in which periodically the state of the art is summarized in review articles such as [6] for the Schottky diode, [8] for the solar cells and [5] for the diode and solar cells, just to cite a few of them. Moreover, the method of I-V characteristic is also used in different research areas, such as, for example, [26].…”
Section: Resultsmentioning
confidence: 99%
“…the temperature. Therefore a practical procedure to evaluate the relevant parameters from a single measure of the current crossing the diode as a function of the applied external voltage V is desirable and it is widely discussed by many authors [4][5][6][7]. In general, the extraction of the parameters of a given model from the measured IV curves is a non-trivial task, since the I-V dependence is usually expressed in an implicit form.…”
Section: Introductionmentioning
confidence: 99%
“…The plot of α versus V allows determining diode parameters. However, Olikh in [4] demonstrates with the synthetic data contaminated with 1% of random noise that the parameter estimation using α versus V plot affects severely due to lack robustness in generating the α − V curve. In the following example we demonstrate how the proposed method provides robust estimate of α − V curve from noisy I-V characteristic.…”
Section: Numerical Tests With Diodementioning
confidence: 99%
“…[1][2][3]. In that the variation of differential conductance (δ G = dI/dV ) with respect to the bias voltage is used in estimating Schottky diode parameters [4][5][6]. Similarly, with a metal oxide semiconductor (MOS) device the important device parameters, such as channel conductance (g d = dI D /dV D ), transconductance (g m = dI D /dV g ), channel mobility (µ 0 ) and threshold voltage (V th ) are obtained from the measurement of drain current (I D ) versus gate-source voltage (V g ) and the drain current (I D ) versus drain-source voltage (V D ) [7] .…”
Section: Introductionmentioning
confidence: 99%